2022
DOI: 10.1007/s11469-022-00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Suicidal Ideation, and Consumption of Psychotropic Drugs During Lockdown by COVID-19 According to Gender and Age

Abstract: The objective was to analyze the relationship between depression and suicidal ideation and psychotropic drugs use during COVID-19 lockdown in adult population considering gender and age. The method used is a descriptive and non-probabilistic study, with a convenience sampling of 3780 participants (70.1% female), aged 18–64 years (M = 37.8). 18.3% participants presented depression and 5.1% exhibited suicidal ideation. The depression rate for female was double (21.4%) than male and 5 times higher (30.2%) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Furthermore, in our study, the students who reported the daily use of psychotropic drugs, compared to those who did not consume such drugs, yielded significantly higher mean scores on the Goldberg total scale and the depression subscale. These data coincide with those of other studies, where a higher level of depression was found to result in increased consumption of psychotropic drugs [ 60 ] and should be considered for the adoption of other measures, such as nutritional interventions complementary to pharmacological treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in our study, the students who reported the daily use of psychotropic drugs, compared to those who did not consume such drugs, yielded significantly higher mean scores on the Goldberg total scale and the depression subscale. These data coincide with those of other studies, where a higher level of depression was found to result in increased consumption of psychotropic drugs [ 60 ] and should be considered for the adoption of other measures, such as nutritional interventions complementary to pharmacological treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In France, similar studies have been conducted using national databases [ 9 , 20 , 21 ], regional [ 13 ] or national military samples [ 22 ]. As in other countries, these studies revealed an increase in psychotropic drug consumption during the pandemic period, particularly notable among young people [ 9 , 13 , 18 , 19 , 23 ] and women [ 13 , 19 , 23 ]. Some of these studies have shown an increase in the consumption of psychotropic drugs among young people in the first few months after the beginning of the pandemic [ 9 , 13 , 19 , 23 ] in relation to schools closures, reduced outdoor activities, and extensive social media use [ 24 26 , 26 , 27 ].…”
Section: Introductionsupporting
confidence: 53%
“…As in other countries, these studies revealed an increase in psychotropic drug consumption during the pandemic period, particularly notable among young people [ 9 , 13 , 18 , 19 , 23 ] and women [ 13 , 19 , 23 ]. Some of these studies have shown an increase in the consumption of psychotropic drugs among young people in the first few months after the beginning of the pandemic [ 9 , 13 , 19 , 23 ] in relation to schools closures, reduced outdoor activities, and extensive social media use [ 24 26 , 26 , 27 ]. In line with a recent study of children and adolescents, the present study confirms that the negative effects on young people did not disappear after the pandemic [ 28 ].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In agreement with the distribution of the sample, a report published during the pandemic showed that females had two times higher rate of depression and younger population had higher odds of mental disorders. 28 Since controls were age-matched to cases, this result could reflect the age group with most patients using psychotropics during the pandemic. Reports revealed that during the COVID-19 pandemic, young adults had a higher risk of developing psychological problems, 29 possibly related to the fear of getting infected or infecting others, 30 job losses, 31 stress, and frailty.…”
Section: Discussionmentioning
confidence: 99%